Mapping cinema memories: Emotional geographies of cinemagoing in Rome in the 1950s. (January 2017) - Ercole, Pierluigi; Treveri Gennari, Daniela; O'Rawe, Catherine
This article, based on the UK Arts and Humanities Research Council–funded project 'In Search of Italian Cinema Audiences in the 1940s and 1950s: Gender, Genre and National Identity', explores the power of geovisualization for capturing the affective geographies of cinema audiences. This mapping technique, used in our project to interrogate the Italian exhibition sector as well as to map film distribution, is used to illustrate the affective and emotional dimensions of cartographic practices related to memory. The article first examines the imbrication of memory and space, before moving on to a discussion of our mapping of the memories of one single respondent and the questions this mapping raises about geographical and remembered space, mobility and the relation between mapping and life-cycles.